NILAI PERUSAHAAN : MANAJEMEN PAJAK, KUALITAS LABA, KEBIJAKAN DEVIDEN DAN TRANSPARANSI SEBAGAI PEMODERASI (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2022)
This research aims to analyze the effect of tax management, earnings quality, and dividend policy on firm value with transparency as a moderating variable. The population in this study all food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016-2019 which numbered 30 companies. The sample was determined using purposive sampling so that a sample of 10 companies with 4 financial reporting periods. The analysis technique used is Moderation Regression Analysis. The results showed that partially tax management and dividend policy had an effect on firm value, while earnings quality had no effect on firm value. The role of corporate transparency as a moderator shows that corporate transparency strengthens the effect of tax management and dividend policy on firm value, while corporate transparency weakens the effect of earnings quality on firm value. The value of the company is an important thing for management to pay attention to in managing the company, so it must pay attention to the things that affect it. Management can carry out information transparency as the main focus in increasing company value, because good transparency will make the company's annual report a source of accurate information for decision makers. Keywords: Dividend Policy, Earnings Quality, Tax Management, Transparency